Energy feasibility study of sludge pretreatments: A review. (1st July 2015) - Cano, R.; Pérez-Elvira, S.I.; Fdz-Polanco, F.
Highlights: Pretreatments to sludge are efficient techniques to improve anaerobic digestion. Most of the pretreatments at lab-scale are not energy feasible in WWTP. Thermal pretreatments have higher energy feasibility than electric ones. Energy self-sufficiency is achieved in thermal hydrolysis plants with a CHP system. Sludge concentration is the key-parameter to reach energy self-sufficiency. Abstract: Most of the pretreatments to sewage sludge in lab-scale studies show high potentials to be implemented in an anaerobic digester since they produce an increase in the biogas production. However, no energy assessments are usually considered in scientific reports. By making a simple evaluation of energy consumption by pretreatments, it can be stated that unfortunately not all the pretreatment technologies have an energy self-sufficiency to be implemented in a WWTP, requiring many times a continuous energy investment. Generally, pretreatments consuming electricity do not satisfy its energy demands from the biogas production in the same process, although high solubilization or biogas production increases are reached. Just ultrasounds applied in full-scale plants, with commercial technologies such as Sonix or Biosonator, provide an energetically self-sufficient pretreatment. In the case of thermal pretreatments, the potential to be implemented with full energy integration is much higher, since they can recover heat from the biogas engine as well as electrical energy in the same extent as for electric pretreatments. This way, full energy integration can be achieved in thermal hydrolysis plants; such is the case of commercial technologies such as Cambi, Exelys (Veolia) or CTH (Aqualogy). Several theoretical approaches and simulations also state that thermal hydrolysis presents a high potential to be fully integrated in WWTP with a complete energy recovery and self-sufficiency.